Positive and Negative Face Dynamics in 'Nanti Kita Cerita tentang Hari' Episode 1: A Pragmatic Analysis of Brown & Levinson's Perspective - Nur'aini, Aisyah (Maliki Interdisciplinary Journal, 2025)
Short movies are not only a way to show social life and entertainment, but also show how each character uses positive face and negative face communication strategies. Positive face and negative face are important to consider to maintain the self-image of speakers and speech partners. Brown & Levinson's politeness theory discusses the face-saving view. The purpose of this study is to analyze the use of positive and negative face communication strategies in the short film “Nanti Kita Cerita Tentang Hari Ini” episode 1 - YouTube channel ToyotaIndonesia. This research uses a descriptive qualitative approach. The data was collected through the listening and note-taking technique, which means watching and observing the entire movie, before recording important information. Furthermore, the data were analyzed using the Miles and Huberman analysis model through the process of presentation, conclusion drawing, and data reduction. This study found 28 data with positive politeness strategies and 14 data with negative politeness strategies. The results show that the dialog between characters in the short film “NKCTHI” episode 1 shows the dynamics of social interaction, and the dialog contains positive and negative face politeness strategies.